GENE-24. ATRX DEFICIENCY IN GLIOMA CELLS OF ORIGIN PROMOTES DISEASE-DEFINING PHENOTYPES BY WAY OF GLOBAL EPIGENOMIC REMODELING. Issue 11 (6th November 2017) - Danussi, Carla; Bose, Promita; Parthasarathy, Prasanna; Silberman, Pedro; Van Arnam, John S; Vitucci, Mark; Tang, Oliver; Heguy, Adriana; Chan, Timothy; Sulman, Erik; Lang, Fred; Creighton, Chad J; et al.
Abstract: Epigenomic abnormalities are increasingly recognized as driver mechanisms in cancer, and somatic mutations in genes encoding epigenetic regulators have now been widely reported across a number of cancer types. Diffusely infiltrating gliomas, feature loss-of function mutations in the SWI/SNF chromatin remodeler gene ATRX as defining molecular alterations delineating major adult and pediatric disease subtypes. Within this disease context, ATRX deficiency invariably co-occurs with mutations in TP53 and in genes encoding either IDH1/2 in adults or H3.3 histone in children. So far, ATRX deficiency has been linked to a wide spectrum of physiological dysfunction, including aberrant gene regulation, abnormal telomere maintenance, genomic instability, and aneuploidy, but the molecular mechanism(s) by which ATRX deficiency promotes oncogenesis are still largely unknown, particularly those involving epigenomic dysregulation. To model these events in putative glioma cells of origin, we inactivated Atrx in primary murine neuroepithelial progenitors (mNPCs). Interestingly, Atrx loss induced NPCs to stop growing as neurospheres and adopt an adherent phenotype, while also exhibiting significantly increased motility. Moreover, when cultured in differentiation conditions, Atrx deficient cells displayed upregulation of astrocyte markers and downregulation of neuronal and oligodendrocyte markers, suggesting that Atrx directly regulates NPCs differentiation state and potential. Notably, the observed phenotypes correlated with altered gene expression profiles involving molecular networks implicated in development, regulation of signal transduction and cellular motility and invasion. Integrating these transcriptional changes with shifts in chromatin accessibility occurring with Atrx deficiency and genome-wide Atrx distribution, as determined by ChIP-seq, revealed highly significant spatial correlations between differentially expressed genes, regions of altered chromatin compaction, histone composition and genomic sites normally occupied by Atrx. Taken together, these findings demonstrate that Atrx deficiency induces widespread disruptions in chromatin organization, which in turn lead to dramatic shifts in gene expression and acquisition of disease-relevant phenotypes in putative glioma cells of origin.